2022
DOI: 10.1126/sciimmunol.abg5539
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptional profiling informs efficient reprogramming of human somatic cells to cross-presenting dendritic cells

Abstract: Type 1 conventional dendritic cells (cDC1s) are rare immune cells critical for the induction of antigen-specific cytotoxic CD8 + T cells, although the genetic program driving human cDC1 specification remains largely unexplored. We previously identified PU.1, IRF8, and BATF3 transcription factors as sufficient to induce cDC1 fate in mouse fibroblasts, but reprogramming of human somatic cells was limited by low efficiency. Here, we investigated single-cell transcriptional dynamics during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…Here we identified 7 DC populations corresponding to 4 different lineages and diverse cell states. We observed that the cDC1 cluster was consistently homogeneous through tissue types, and its identity was dictated by the IRF8 and STAT2 regulons, as described previously (48, 49). Interestingly, cDC1s also featured high regulon activity and expression of SMARCA5 .…”
Section: Discussionsupporting
confidence: 83%
“…Here we identified 7 DC populations corresponding to 4 different lineages and diverse cell states. We observed that the cDC1 cluster was consistently homogeneous through tissue types, and its identity was dictated by the IRF8 and STAT2 regulons, as described previously (48, 49). Interestingly, cDC1s also featured high regulon activity and expression of SMARCA5 .…”
Section: Discussionsupporting
confidence: 83%
“…For instance, direct reprogramming of fibroblasts to neurons requires the transcription factors ASCL1, BRN2 and Myt1l [144], while hemogenic reprogramming depends on GATA2, GFI1B and FOS expression [145]. Efficient reprogramming of somatic cells to hepatocytes [146] and cross-presenting dendritic cells (cDC1s) [147] has also been described. Further studies will elucidate which specific reprogramming machineries are required to induce additional cell identities.…”
Section: Perspectivesmentioning
confidence: 99%
“…Given the importance of DCs in immunity, and their distinctive phenotype and functions compared to other myeloid components including macrophages and monocytes, the lack of laboratory models of these cells is becoming a critical bottleneck for the field. The current in vitro models of human DC biology rely on the differentiation of CD34+ hematopoietic stem cells (HSC) from blood or bone marrow (Balan et al, 2014), are differentiated in vitro from peripheral blood monocytes (Pacis et al, 2015), or use induced pluripotent stem cells (iPSC)(Monkley et al, 2020) or directed differentiation from fibroblasts (Rosa et al, 2018, 2022). Concordance between cord-blood derived cDC1 with their in vivo blood counterparts was previously reported (Balan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%